Analysis of the Sustainability of Tilapia (Oreochromis niloticus) Fish Cultivation Business in Muara Tami District, Jayapura - Arismon, Donni; Cahyono, Indra; Heriansah, Heriansah (Agrikan Jurnal Agribisnis Perikanan, 2023)
There are several threats to the sustainability of the Tilapia fish cultivation business in the Muara Tami District, which is one of the Tilapia fish production centers in Jayapura, Papua Province. The research was carried out with the aim of analyzing the sustainability of fish cultivation development in the Muara Tami District, Jayapura City, carried out from October to December 2023 with interviews with 30 fish cultivators, data processing and analysis methods using Multi-Dimensional Scaling-Rapid Appraisal for Sustainability ( MDS-Raps) which is a modification of Rapid Appraisal for fisheries (Rapfish). The research results show that the sustainability status of fish farming in the Muara Tami District in the ecological, social, economic, technological and institutional dimensions (multidimensional analysis) is 36.63% in the less sustainable category and the results of the analysis show that the sustainability dimension that has the largest index value is the economic dimension. So a simultaneous strategy is needed for all four dimensions to develop and improve indicator attributes in the social, ecological and technological dimensions, especially in the institutional dimension.